Interactive and Digital-based Learning Media in Blended Classrooms: The Teachers’ Needs, Beliefs and Reflection - Nora Fudhla (Universitas Negeri Padang, 2023)
This article aims at describing the results of needs analysis and training conducted for teachers in SMAN 1 V Koto Kp Dalam Pd Pariaman. The training given was an offered solution to teachers’ need for assistance and guidance in developing interactive and digital-based learning media for blended classrooms. A certain digital app, namely Canva was given as training materials based on the results of teachers’ needs and school accommodations. After 8 meetings of training, the teachers successfully created their interactive and multimedia teaching media which were taken into practice in blended classrooms. It was revealed that students showed positive responses which boost their motivation to learn. The teacher concluded that the help of advanced technology surely increased the learning results and students' interest. This belief is somehow counter-attacked by some after-teaching reflection that depicts the drawbacks of the internet and gadgets during blended classrooms. Therefore, it is suggested for that teachers do more supervision and repair the product for better improvement in future teaching practices.